THU0252 Relationship between Lymphocyte Count and Risk of Infection in Rheumatoid Arthritis Patients Treated with Tofacitinib. (23rd January 2014) - van Vollenhoven, R.; Riese, R.; Krishnaswami, S.; Kawabata, T.; Fosser, C.; Rottinghaus, S.; Lamba, M.; Zwillich, S. H.; Bradley, J.
Abstract : Background: Tofacitinib is a novel oral Janus kinase (JAK) inhibitor for the treatment of rheumatoid arthritis (RA). Cytokines (e.g., interleukin (IL)-2, -4, -7, -15, -21) involved in lymphocyte development, function and homeostasis are known to signal through JAK. Objectives: To characterise changes in absolute lymphocyte counts (ALC) following tofacitinib treatment and evaluate the relationship between ALC and rates of infection. Methods: ALC and adverse event data of treated (requiring antimicrobial therapy or surgical intervention; TI), serious (SI), and opportunistic infections (OI) were analysed from 5 randomised controlled Phase 3 (P3), and 2 open-label long-term extension (LTE) studies in patients (pts) with RA. Lymphopenia was defined by OMERACT criteria (ALC ×1000/mm 3 ) as mild, ≥1.5 to <2; moderate to severe, <1.5 to ≥0.5; and potentially life threatening, <0.5. Confirmed lymphopenia was defined as lymphopenia in 2 consecutive measurements. Cox analysis was applied to evaluate the relationship between "time-varying" ALC and rates of infection. Threshold values of ALC were evaluated by calculating the percentage of correct decisions (POCD), based on the sum of pts falling below a specific threshold (e.g. 0.5 or 1.0) and experiencing an SI, and those with ALC above threshold and without an SI. Results: Across treatment groups, at baseline 35-39% of pts in P3 (N = 3252) had ALC of <1.5. Pooled analysis of P3 data showed mean increases in ALC from baseline with tofacitinib at Month 1 followed by a gradual decrease of approximately 10% from baseline after 12 months of therapy. Further decreases in mean ALC were not seen in the LTE studies. The frequency of lymphopenia in the P3 studies was similar between tofacitinib and placebo pts at Months 3 and 6; all placebo pts were advanced to tofacitinib at Month 6. Lymphocyte subset analyses from Phase 2 (P2) dose-ranging studies (6 and 24 weeks) showed increases in B cell counts (~40%; 1-24 weeks), decreases in NK cell counts (~40%; Weeks 2-24) and a transient increase in T cell counts (Weeks 1-2). Subset analyses from LTE studies (median exposure 22 months) showed that NK cell counts were similar to baseline counts, B cell counts remained elevated and T cell counts decreased slightly (<20%). For pts with ALC ≥0.5, there was no increase in the frequency of TI, SI or OI. Although confirmed lymphopenia of <0.5 was infrequent (5/2430 pts (0.2%) in P3; 10/3219 (0.3%) in the LTE), 11, 4, and 1 of these pts experienced a TI, SI, and OI, respectively. The SI in this group included one case each of pneumonia, cellulitis, tuberculosis (an OI), and pyelonephritis. Cox analysis using all available P2, P3 and LTE data showed a statistically significant trend (p<0.05) for increased risk for infection (serious and opportunistic) with decreased ALC. The POCD decreased from approximately 94% for an ALC threshold of 0.5 ×1000/mm 3 to 66% for 1.0 ×1000/mm 3 . Conclusions: Tofacitinib treatment in patients with moderate to severe RA is associated with modest mean decreases in ALC over 12 months of therapy. Confirmed ALC <0.5×1000/mm 3 occurred rarely and may be the optimum threshold for defining increased risk of serious infection. These data could inform appropriate risk mitigation strategies. Disclosure of Interest: R. van Vollenhoven Grant/research support from: AbbVie, BMS, GSK, MSD, Pfizer, Roche, UCB, Consultant for: AbbVie, BMS, GSK, MSD, Pfizer, Roche, UCB, R. Riese Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., S. Krishnaswami Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., T. Kawabata Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., C. Fosser Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., S. Rottinghaus Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., M. Lamba Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., S. Zwillich Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., J. Bradley Shareholder of: Pfizer Inc., Employee of: Pfizer Inc.